Kombinasi Senam Hipertensi dan Terapi Musik Suara Alam Mampu Menurunkan Tekanan Darah Pada Penderita Hipertensi - Diah Nur Kafitri; Linda Sofiana Rohmah; Karin Mitha Astary; Virgianti Nur Faridah; Rizky Asta Pramestirini (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Hypertension is a health problem that is quite dangerous in the world, because it is a major risk factor for cardiovascular disease. Hypertension can be treated with nonpharmacological therapies, such as hypertension exercise and natural music therapy. The purpose of this study was to determine the effect of a combination of hypertension exercise and natural sound music therapy on reducing blood pressure in hypertension sufferers in the working area of ​​the Modo Health Center. The research design used a pre-experimental one group pre-post test design on 52 hypertensive patients who were selected using a consecutive sampling technique from a total population of 109. The intervention was in the form of giving a combination of hypertension exercise and natural sound music for 10-15 minutes according to the SOP for hypertension exercise and natural sound music. After that, it was analyzed using paired t-test. The results showed that the average blood pressure before treatment was 168.77/95.12 mmHg. After being given treatment the average blood pressure was 156.69/85.88 mmHg. The results of the pre-post systolic and pre-diastolic statistical tests obtained a significance value of p=0.000 (p<0.005), which means that there is an effect of a combination of hypertension exercise and natural sound music therapy on reducing blood pressure. The mechanism for reducing blood pressure after exercise is because exercise can relax blood vessels, so that by dilating blood vessels blood pressure will decrease. Providing natural sound music therapy can cause relaxation of arteriolar smooth muscles which play an important role in maintaining blood pressure. It is hoped that the combination of hypertension exercise and natural sound music therapy can be applied as an intervention at the Prolanis Health Center in Modo.